2016
DOI: 10.1111/cas.13018
|View full text |Cite
|
Sign up to set email alerts
|

Podocalyxin‐like protein, linked to poor prognosis of pancreatic cancers, promotes cell invasion by binding to gelsolin

Abstract: The cell‐adhesion glycoprotein PODXL is associated with an aggressive tumor phenotype in several forms of cancer. Here, we report that high PODXL expression was an independent predictor of worse overall survival of pancreatic cancer patients, and that PODXL promoted pancreatic cancer cell motility and invasion by physically binding to the cytoskeletal protein gelsolin. Suppression of PODXL or gelsolin decreased membrane protrusions with abundant peripheral actin structures, and in turn inhibited cell motility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 41 publications
2
58
0
Order By: Relevance
“…Although typically absent in normal pancreas and nonmalignant pancreatic epithelial cells, approximately 30% to 69% of pancreatic ductal adenocarcinomas (PDAC) express PODXL, with the strongest expression exhibited by the invasive front of primary tumors (12,21,22). Moreover, high PODXL expression is associated with poor clinicopathologic characteristics and the development of distant metastasis (23,24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although typically absent in normal pancreas and nonmalignant pancreatic epithelial cells, approximately 30% to 69% of pancreatic ductal adenocarcinomas (PDAC) express PODXL, with the strongest expression exhibited by the invasive front of primary tumors (12,21,22). Moreover, high PODXL expression is associated with poor clinicopathologic characteristics and the development of distant metastasis (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high PODXL expression is associated with poor clinicopathologic characteristics and the development of distant metastasis (23,24). PODXL has also been shown to be an independent predictor of poor prognosis and is linked to higher risk of death and reduced survival (10,(22)(23)(24). These effects are hypothesized to be at least partially due to the ability of PODXL to regulate cell migration and invasion (22,24).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, PODXL expression was reported to be associated with tumor aggression and adverse prognosis in several cancers, such as, urothelial bladder cancer [8], colorectal cancer [10], pancreatic cancer [11], hepatocellular carcimoma [9] and GC [12]. Emerging evidence revealed that the altered expression of PODXL was implicated with migration, epithelial-mesenchymal transition (EMT), invasion and metastasis of cancers [11, 13, 14]. Lin et al [13] demonstrated that the level of PODXL was closely correlated with motility and invasiveness of breast cancer cells via activating the Rac1/Cdc42/cortactin signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Podocalyxin‐like protein was expressed in diverse malignancies, and its overexpression was linked to a poor prognosis of cancer patients, including prostate cancer, urothelial bladder cancer, colorectal cancer, glioblastoma, pancreatic cancer and lung adenocarcinoma patients . High PODXL expression was associated with features such as large tumor size, high histological grade and undetectable expression of the estrogen and progesterone receptors .…”
Section: Introductionmentioning
confidence: 99%